2011
DOI: 10.1111/j.1440-1746.2011.06718.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post‐endoscopic retrograde cholangiopancreatography pancreatitis by epinephrine sprayed on the papilla

Abstract: Epinephrine sprayed on the papilla may be effective to prevent PEP. Female patients (aged ≥ 18 years and < 35 years) (7/40, 17.5%), common bile duct diameter < 10 mm (27/40, 67.5%), previous cholangitis (3/40, 7.5%), body mass index ≥ 24 (22/40, 55%), and/or serum triglycerides ≥ 5.65 mmol/L (6/40, 15%), might be risk factors for post-ERCP pancreatitis, but are not statistically significant in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
3
36
0
2
Order By: Relevance
“…There were two RCTs comparing topical epinephrine with placebo and these were conducted at different centres in Asia . The primary limitations of these studies were that they included only patients undergoing diagnostic ERCP and both utilised an ERCP protocol that mandates that a more experienced endoscopist complete difficult procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two RCTs comparing topical epinephrine with placebo and these were conducted at different centres in Asia . The primary limitations of these studies were that they included only patients undergoing diagnostic ERCP and both utilised an ERCP protocol that mandates that a more experienced endoscopist complete difficult procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The primary limitations of these studies were that they included only patients undergoing diagnostic ERCP and both utilised an ERCP protocol that mandates that a more experienced endoscopist complete difficult procedures. While patients undergoing diagnostic ERCP are typically considered to be at low risk for PEP, it should be noted that, in the epinephrine trial conducted by Xu et al ., 9% of the patients had acinarisation and the mean number of pancreatic duct contrast injections was 4.6. This suggests that many patients became high risk due to procedural interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent two meta-analyses of 10 RCTs (1554 patients and 1730 patients respectively) have concluded that allopurinol does not reduce post-ERCP pancreatitis and should be not recommended as a prophylactic agent [63,64] . Other agents studied (Adrenaline spray, pentoxifylline, platelet-activating factor acetylhidrolase, semapimod, aprepitant and risperidone) have either revealed discordant results or no effect on preventing post-ERCP pancreatitis [64][65][66][67][68][69][70][71][72][73] .…”
Section: Interruption Of Inflammatory Cascade (Anti-inflammatory): Nomentioning
confidence: 99%
“…The results also showed no difference of overall PEP between the combined and indomethacinalone therapy (6.7% vs 6.4%), which was consistent with the findings of our study. Rectal indomethacin has been used increasingly since the publication of the study by Elmunzer et al 3 Although not reported, rectal indomethacin was less likely be administrated in patients in 2 well-conducted randomized controlled trials from Xu et al 6 and Matsushita et al 7 related to epinephrine spraying for PEP prevention, both of which were finished before 2011. All patients in the current study received rectal indomethacin before ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…It may prevent PEP through direct relaxation of the sphincter of Oddi and reduction of papillary edema by decreasing capillary permeability, as shown in 2 randomized trials. 6,7 A meta-analysis suggested that papillary epinephrine spraying and rectal NSAIDs are the 2 most efficacious agents for PEP prevention. 8 We hypothesized that the combination of rectal indomethacin and papillary epinephrine spraying, which counteract the pathogenesis of PEP in different ways, may prevent PEP more vigorously.…”
Section: See Related Editorial On Page 1446mentioning
confidence: 99%